Corrigendum to: Kawiryan Discourse as The Legitimacy of The Islamic Sultanate in Serat Saptastha - Suwito NS (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
Corrigendum to: Ilafi, A., Sudardi, B., & Supana, S. (2018). Kawiryan Discourse as The Legitimacy of The Islamic Sultanate in Serat Saptastha. IBDA` : Jurnal Kajian Islam Dan Budaya, 16(1). https://doi.org/https://doi.org/10.24090/ibda.v16i1.1396, in the PDF fulltext article, first author name typed as "Afiliasi Ilafi Supana". Last name deleted, so the author's full name is "Afiliasi Ilafi".